IMPLEMENTASI KOMPETENSI PEDAGOGIK DAN PROFESIONAL GURU DALAM MEMBENTUK KARAKTER PESERTA DIDIK - Kurniasih, Dedeh; H. Babang Robandi; Yusri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article discusses the implementation of teachers' pedagogical and professional competencies in shaping students' character. Pedagogical competence, which includes understanding and applying effective learning principles, as well as professional competence, which focuses on mastery of subject matter and curriculum development, plays an important role in forming students' positive attitudes and behaviors. This study aims to examine the relationship between these two competencies and character formation, such as moral values, discipline, and responsibility. The findings show that the development of both pedagogical and professional competencies can create a learning environment that supports the strengthening of students' character, both in the classroom context and in daily interactions. Therefore, improving teachers' competencies is crucial to achieving educational goals that focus not only on cognitive aspects but also on the affective aspects of students.